Minimally Invasive Management of Abdominal Trauma - Ritter, Kaitlin A.; Claridge, Jeffrey A.; El-Hayek, Kevin (Digestive Disease Interventions, 2018)
Management of traumatic abdominal injuries has traditionally relied upon a combination of systematic physical examination, image-guided evaluation, clinical judgment, and, when necessary, maximally invasive surgical intervention. Advances in the fields of interventional radiology, endoscopy, and laparoscopy have altered these traditional treatment algorithms. As growth of these techniques continues, an increasing number of minimally invasive strategies are available to clinicians for the management of abdominal trauma. Here reviewed is a brief overview of minimally invasive strategies for the management of non–solid organ abdominal trauma with a focus on new, minimally invasive diagnostic and treatment tools.
Keywords: abdominal trauma; critical care; minimally invasive